Severe Fournier’s gangrene - a conjoint challenge of gynaecology and plastic surgery - Wähmann, Matthias Stefan Theodor; Schütz, Florian; Sohn, Christof; Schott, Sarah (Journal of surgical case reports, 2017)
Abstract. Necrotizing fasciitis (NF) is a rare soft tissue infection characterized by rapidly progressing necroses and a high mortality
Published: 08 December 2017
Angabe Frontdoor: Heft 12
Gesehen am 28.06.2018